Tri‐orthogonal polarization diversity reception for non‐geosynchronous satellite orbit ionospheric channels - Lawrence, Nicholas P.; Hansen, Hedley J.; Abbott, Derek (International journal of satellite communications and networking, 2018)
Summary Electromagnetic signals propagating through the ionosphere are subject to path delay and the depolarizing effect of Faraday rotation. These are both dependent on global position and link geometry, which constantly vary for satellites in non‐geosynchronous orbits. These effects introduce performance error and reduce range resolution of remote sensing polarimetric measurements. Communication with ground receivers may be severely degraded by these effects. In this paper, a tri‐orthogonal approach at the receiver is introduced to enhance performance of conventional polarization diverse receive schemes. Performance is measured through a capacity metric. The work presented forms part of a large‐field‐of‐view, non‐geosynchronous satellite model exploiting tri‐orthogonal receive polarimetry as a means to enhancing link performance in a field‐of‐view. Copyright © 2016 John Wiley & Sons, Ltd. Diversity is known to offer advantages for communication links. We present simulations of satellite systems using real‐time ionospheric and orbital data to illustrate the benefit of tri‐orthogonal polarization diversity at the ground receiver. Through no alteration to the satellite, the approach suggests that increased diversity gain is offered for all systems considered over standard reception techniques.